Analisis Unsur Pokok Musikal Gending Arje pada Gendang Beleq Telaga Waru Pedaleman Daya Kotaraja - Hafiz, Alwan; Markarma, Ridwan; Izzah, Ismatul (TAMUMATRA, 2020)
This study aimed to know and describe the main elemen musical of gending arje in gendang beleq telaga waru of pedaleman daye at kotaraja by using music and song theory. This study was used deskriptif qualitative. Base and result showed that the main musicalof gending arje in gendang beleq telaga waru had asection of song form, homophonis texture. In rhythm music tolls (gendang and kenceng or cemprang) was used rhapsoldic rhythmic and resultant rhythm which was only in gendang music tool. Chord melodiy in gendang beleq telaga waru of pedaleman daye was paudan kemuning